P14.33 Adult brainstem gliomas in neurofibromatosis type 1 (NF1). (6th September 2019) - Guillamo, J; Wang, A; Ducray, F; Barbarot, S; Chinot, O; Frappaz, D; Bauchet, L; Wolkenstein, P; Laigle-Donadey, F
Abstract: BACKGROUND: The brainstem is the second location of brain tumors after optic pathways in NF1. In NF1 children, brainstem gliomas are usually indolent and have a better prognosis than their counterparts in non NF1 children. In contrast, the natural history and prognosis of adult brainstem gliomas in NF1 are nearly unknown. MATERIAL AND METHODS: We conducted a retrospective analysis of medical records and MRI of adult NF1 patients followed for a brainstem glioma in 8 centers over a 17 years period (2000–2017). Clinical and imaging characteristics, management and outcome were analyzed. RESULTS: Twenty five patients were included in the study (13 males and 12 females) with a median age of 32 (range 17–58). The epicenter of the tumor was located into the pons n=13 (52%), the mesencephalon n=7 (28%), the medulla oblongata n=5 (20%). On MRI, contrast enhancement was seen in 19 tumors (76%). Pathological examination was available in 13 tumors (52%) and showed a high grade astrocytoma (III or IV) in 9 tumors. Five patients were asymptomatic, 3 remained asymptomatic during the follow-up (median follow-up: 86 months, range 22–124). Twenty patients were symptomatic with a median duration of symptom of 2.5 months (range 1–10) before diagnosis. Among these symptomatic patients, 15 died from tumor progression despite treatment with radiation therapy and or chemotherapy. The median overall survival of symptomatic patients was 36 months. CONCLUSION: Brainstem gliomas are rare tumors in adults with NF1. Unlike children, adult brainstem gliomas seem to have an unexpected poor prognosis, suggesting the disease may be different in adulthood.